2024
DOI: 10.1039/d4ta01952k
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar conjugated microporous polymer anchoring graphene hybrids for high-performance zinc–organic batteries

Chengmin Hu,
Yumin Chen,
Ziyang Song
et al.

Abstract: Redox organic polymers have emerged as cathode candidates for zinc−organic batteries (ZOBs) due to their high electrochemical activity, environmental friendliness and structural designability. However, most organic polymers are confined to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In previous reports, it has been demonstrated that carbon coating strategies can improve gas adsorption capacity and modulate the accessibility of electrocatalysts to protons, 113 thereby reducing HER competition and increasing NRR activity. The preparation of CoP particles confined in situ in carbon nanotubes (CoP/CNT) (structure as in Figure 5c) to be used as NRR catalyst was first reported by Meng et al 83 The oxygen inclusion during the synthesis led to the oxygenrich copper cluster products (O-CoP/CNT), and it anchored the clusters firmly to the carbon nanotubes and stabilized the intermediates from NRR, through additional hydrogen bonding interaction, to enhance the NRR activity.…”
Section: Cobalt Phosphidementioning
confidence: 99%
“…In previous reports, it has been demonstrated that carbon coating strategies can improve gas adsorption capacity and modulate the accessibility of electrocatalysts to protons, 113 thereby reducing HER competition and increasing NRR activity. The preparation of CoP particles confined in situ in carbon nanotubes (CoP/CNT) (structure as in Figure 5c) to be used as NRR catalyst was first reported by Meng et al 83 The oxygen inclusion during the synthesis led to the oxygenrich copper cluster products (O-CoP/CNT), and it anchored the clusters firmly to the carbon nanotubes and stabilized the intermediates from NRR, through additional hydrogen bonding interaction, to enhance the NRR activity.…”
Section: Cobalt Phosphidementioning
confidence: 99%
“…With the intensification of environmental pollution and the energy crisis, the development of sustainable energy storage systems has become a priority in energy conversion. Recognized for high energy density and long cycle stability (250–400 Wh kg –1 ), lithium-ion batteries (LIBs) have played a crucial role in portable electronics and electric vehicles. However, the scarcity of lithium resources and flammability of organic electrolytes hinder the specific applications of LIBs. Therefore, it is significant to explore advanced energy storage systems to replace LIBs. Aqueous zinc-ion batteries (ZIBs), including a stable Zn metal anode, an electrolyte with high Zn 2+ ions transmission, and structurally adjustable cathode materials, have emerged as potent contenders for the forthcoming advanced energy storage system. …”
Section: Introductionmentioning
confidence: 99%